The Relationship between Coronavirus Anxiety, Resilience, and Islamic Beliefs in Hemodialysis Patients during the Pandemic: A Survey in Iran - Somayeh Hayati; Rezvaneh Manzour; Fatemeh Haj Hashemi; Ahmad Rajab Dizavandi (Islamic Guidance and Counseling Journal, 2023)
The coronavirus disease has been converted into one of the greatest present public health crises. Patients with chronic diseases, including people with kidney failure undergoing hemodialysis treatment, are one of the main groups at risk of coronavirus. The present study aimed at investigating the relationship between coronavirus anxiety, resilience, and religious beliefs in hemodialysis patients during the Covid-19 pandemic in Iran. A total of 160 patients undergoing hemodialysis participated in this cross-sectional study. The data was collected by convenient sampling from three hemodialysis centers from April 15 to May 15, 2022, in Northern Khorasan province. Patients completed four questionnaires: demographic information questionnaires, Corona Disease Anxiety Scale (CDAS), Connor-Davidson Resilience Scale (CD-RISC), and Golriz and Baraheni's Religious Attitude (2013). Data were analyzed using Stata14. The findings showed that 98.8% of the participants had mild anxiety and 1.2% had moderate anxiety. Anxiety (the physical component) had an inverse relationship with resilience (the control component) (P < .05); also, resilience and its components had a direct correlation with religion (P < .05). Resilience and religious beliefs are related to corona anxiety in hemodialysis patients, and targeting these two components through psychological treatments can be effective in reducing corona anxiety.